So much to offer: an exploration of learning and cultural wealth with Roma Slovak post-16 students. Issue 1 (2nd January 2022) - Doyle, John
ABSTRACT: The newly arrived Roma Slovak community in a large urban city in the north of England has been widely perceived as having a myriad of social problems and there is a conflict with the wider community. This paper presents the results of a project to explore barriers and possibilities for the social and educational integration of newly arrived Roma Slovak migrants in the UK. The research carried out ethnographic fieldwork in a post-16 service for young people, using a CRT approach based on Yosso's community cultural wealth model. The paper also applies an intersectional analysis and problematises assumptions that portray Roma communities as homogeneous, marginalised, and uncritically family oriented. The findings recover the voices and perspectives of the Roma Slovak community from a critical, though positive, perspective. The Roma Slovak students' stories that emerged from this research are in stark contrast to the negative stereotypes commonly shared about the community.